Fabrication of ZIF-8@SiO2 Core-Shell Microspheres as the Stationary Phase for High-Performance Liquid Chromatography - Fu, Yan-Yan; Yang, Cheng-Xiong; Yan, Xiu-Ping (Chemistry : a European journal, 2013)
The unique features of high porosity, shape selectivity, and multiple active sites make metal–organic frameworks (MOFs) promising as novel stationary phases for high‐performance liquid chromatography (HPLC). However, the wide particle size distribution and irregular shape of conventional MOFs lead to lower column efficiency of such MOF‐packed columns. Herein, the fabrication of monodisperse MOF@SiO2 core–shell microspheres as the stationary phase for HPLC to overcome the above‐mentioned problems is reported. Zeolitic imidazolate framework 8 (ZIF‐8) was used as an example of MOFs due to its permanent porosity, uniform pore size, and exceptional chemical stability. Unique carboxyl‐modified silica spheres were used as the support to grow the ZIF‐8 shell. The fabricated monodisperse ZIF‐8@SiO2 packed columns (5 cm long × 4.6 mm i.d.) show high column efficiency (23 000 plates m−1 for bisphenol A) for the HPLC separation of endocrine‐disrupting chemicals (bisphenol A, β‐estradiol, and p‐(tert‐octyl)phenol) and pesticides (thiamethoxam, hexaflumuron, chlorantraniliprole, and pymetrozine) within 7 min with good relative standard deviations for 11 replicate separations of the analytes (0.01–0.39, 0.65–1.7, 0.70–1.3, and 0.17–0.91 % for retention time, peak area, peak height, and half peak width, respectively). The ZIF‐8@SiO2 microspheres combine the advantages of the good column packing properties of the uniform monodisperse silica microspheres and the separation ability of the ZIF‐8 crystals. Core strength: Monodisperse ZIF‐8@SiO2 (ZIF‐8=zeolitic imidazolate framework 8) core–shell microspheres have been fabricated through controllable growth of a ZIF‐8 shell on spherical carboxylate‐terminated SiO2 cores (see figure). The metal–organic framework material is suitable as a stationary phase for fast and highly efficient HPLC separation.